Track plate anchor mortar and preparation method thereof

By using modified polymer emulsion and crack-resistant fibers in the track plate anchor mortar, the problem of mortar loss of water, shrinkage and cracking at high temperatures is solved, and the construction efficiency and durability of the track plate are improved by adjusting the solidification time.

CN116409976BActive Publication Date: 2025-02-18BEIJING RUNHIGH SCI & TECH +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310183532.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-01
Publication Date
2025-02-18
Estimated Expiration
2043-03-01

AI Technical Summary

Technical Problem

The existing track plate anchor mortar is prone to water loss, shrinkage and cracking in high temperature environments, and the solidification time is unstable, which affects the construction efficiency and durability of the track plate.

Method used

Using components such as modified polymer emulsion and crack-resistant fibers, the lubrication and plasticization of the modified polymer emulsion is combined with the physical enhancement of crack-resistant fibers to reduce the water loss rate of the mortar at high temperatures, and through the adjustment of the flow Change the amount of the modified polymer emulsion and adjust the solidification time of the mortar.

Benefits of technology

It effectively prevents the water loss of the anchor mortar from being solidified, improves the lubricating effect and extrusion lubricity of the mortar, extends the durability of the track plate, and ensures the operability of the construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004103009100000071
    Figure BDA0004103009100000071
  • Figure BDA0004103009100000081
    Figure BDA0004103009100000081
  • Figure BDA0004103009100000082
    Figure BDA0004103009100000082
Patent Text Reader

Abstract

The present invention relates to the technical field of building engineering materials, and specifically discloses a track plate anchor mortar, comprising the following raw material components in parts by weight: 40-60 parts of cement, 0-20 parts of mineral admixture, 40-50 parts of fine aggregate, 0.1-0.8 parts of water reducing agent, 0.2-1 parts of water retaining agent, 0.1-0.5 parts of anti-cracking fiber, 1-3 parts of expansion agent, 0.3-1 parts of waterproofing agent, 0.2-1 parts of steel bar preservative, 0-4 parts of retarder, and 10-18 parts of modified polymer emulsion. The anchor mortar provided by the present invention significantly improves the freeze-thaw resistance of the anchor sealing part through the synergistic effect between the components, and also ensures the anti-corrosion effect, thereby extending the durability of the track plate, and by adopting the modified polymer emulsion, the consistency of the operation time during construction is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building engineering materials, and in particular to a track plate anchor sealing mortar and a preparation method thereof. Background Art

[0002] With the development of high-speed railways in my country, ballastless tracks have gradually replaced ballasted tracks due to their good smoothness and stability. Currently, the most widely used are CRTSⅠ slab ballastless tracks, CRTSⅡ slab ballastless tracks and CRTSⅢ slab ballastless tracks. The ends of the embedded steel bars of the above-mentioned prestressed concrete track slabs are all reserved with anchor holes. After the track slabs are formed, steamed and demolded, they need to be sealed with anchor mortar, and then put into water for further maintenance. The quality of the anchor hole sealing directly affects the quality of the track slab. If the anchor hole sealing is cracked or separated from the base, the prestressed steel bars will be exposed to the air and water, and the steel bars will be rusted, which will affect the durability of the track slab.

[0003] According to the track slab manufacturing process, after the track slab has been steamed and cured, it is necessary to carry out anchor sealing construction after the formwork is removed. At this time, the track slab is still in a high temperature state of 40-50℃. After the anchor hole sealing operation, the anchor sealing mortar will lose water due to heat before solidification, and the edge of the anchor hole is prone to shrinkage and cracking.

[0004] Existing technical solutions usually add expansion agents or shrinkage reducers to the formula, but these two methods only expand or reduce the mortar after it solidifies, and fail to solve the problem of water loss, shrinkage and cracking before the mortar solidifies; in addition, since the hydration reaction rate of cement is related to temperature, the solidification time of the anchor mortar will also be affected by the ambient temperature, shortening the solidification time when the temperature rises and extending the solidification time when the temperature drops. In actual construction, a too short solidification time will result in insufficient operating time, and a too long solidification time will result in failure to timely enter the water for curing. In addition, in many areas, the temperature difference during the day is large, and the mortar with a fixed mix ratio cannot simultaneously meet the construction requirements of different time periods. Therefore, a new type of track plate anchor mortar is urgently needed. Summary of the invention

[0005] Aiming at the shortcomings of existing anchor sealing mortars, such as low strength, easy cracking, unstable setting time, etc., the present invention provides a track plate anchor sealing mortar.

[0006] In addition, the present invention also provides a method for preparing track slab anchor sealing mortar.

[0007] In a first aspect, the present invention provides a track plate anchor mortar, which adopts the following scheme:

[0008] A track plate anchor sealing mortar, comprising the following raw material components in parts by weight: 40-60 parts of cement, 0-20 parts of mineral admixture, 40-50 parts of fine aggregate, 0.1-0.8 parts of water reducing agent, 0.2-1 parts of water retaining agent, 0.1-0.5 parts of anti-cracking fiber, 1-3 parts of expansion agent, 0.3-1 parts of waterproofing agent, 0.2-1 parts of steel bar preservative, 0-4 parts of retarder, and 10-18 parts of modified polymer emulsion;

[0009] The modified polymer emulsion comprises the following raw material components in parts by weight: 3-8 parts of aluminum dihydrogen phosphate, 5-10 parts of magnesium aluminum silicate, 10-20 parts of glass microspheres, 52-77 parts of water, 5-10 parts of silane coupling agent solution, 1-3 parts of penetrant, and 10-20 parts of plasticizer.

[0010] The anchor mortar provided by the present invention is added with anti-cracking fibers and water-retaining agents. The water-retaining agents can reduce the water loss rate of the anchor mortar in a high temperature environment, and the anti-cracking fibers can play a role of physical reinforcement and toughening in the unsolidified mortar. The composite effect of these two components can ensure that the anchor mortar will not lose water, shrink, or crack due to high temperature when it is not solidified. In addition, on the basis of adding the steel bar preservative, waterproofing agents and penetrants are added, wherein the waterproofing agent can improve the water resistance of the mortar and prevent moisture from entering the mortar when the anchor is put into water for maintenance. The penetrant can enhance the combination of the mortar and the anchor hole interface to make it more dense and better sealed, and can effectively prevent moisture and air from invading from the interface. The synergistic effect of the steel bar preservative, waterproofing agent, and penetrant significantly improves the freeze-thaw resistance of the anchor part and ensures the anti-corrosion effect, thereby extending the durability of the track plate.

[0011] The present invention adopts a modified polymer emulsion, wherein the glass microspheres are in a microsphere structure, providing a ball lubrication effect, the lithium magnesium silicate is in a layered structure, providing a sliding lubrication effect, and the aluminum dihydrogen phosphate provides a certain viscosity-increasing effect. The combined effect of the three provides an excellent lubrication effect, so that the anchor mortar has good extrusion lubricity. The added plasticizer can enhance the thixotropy of the mortar and prevent sagging after anchor sealing. The modified polymer emulsion itself has the effects of lubrication and plasticization. Therefore, compared with the polymer emulsion provided by the prior art solution, the dosage can be adjusted within a certain range without affecting the operability of the anchor mortar. Since the setting time of cement is affected by the amount of water added, the mixing water amount of the anchor mortar can be changed by changing the amount of rheology-modified polymer emulsion, thereby adjusting the setting time of the anchor mortar.

[0012] Preferably, the water reducer is at least one of a melamine-based water reducer, an aminosulfonate-based water reducer or a polycarboxylic acid-based water reducer; and / or

[0013] The water retaining agent is at least one of cellulose ether, polyacrylamide or wood fiber; and / or

[0014] The anti-cracking fiber is at least one of polypropylene fiber, glass fiber and basalt fiber; and / or

[0015] The expansion agent is at least one of a UEA expansion agent, a calcium sulfoaluminate expansion agent or a magnesium oxide expansion agent; and / or

[0016] The waterproofing agent is at least one of modified sheet silicate, sodium methyl silicate, potassium methyl silicate or zinc stearate; and / or

[0017] The steel bar rust inhibitor is at least one of benzotriazole, calcium nitrite or fatty alcohol amine; and / or

[0018] The retarder is at least one of sucrose, gluconic acid, boric acid, tartaric acid or sodium pyrophosphate.

[0019] Preferably, the cement is at least one of ordinary Portland cement, sulphoaluminate cement or aluminate cement; and / or

[0020] The mineral admixture is at least one of mineral powder, tailings powder, fly ash or silica powder; and / or

[0021] The fine aggregate is at least one of river sand, quartz sand, mineral sand or calcium sand.

[0022] Preferably, the polymer emulsion is at least one of epoxy emulsion, polyurethane emulsion, phenolic resin emulsion, silicone emulsion, vinyl resin emulsion, emulsified rubber, emulsified asphalt, silicone-acrylic emulsion, styrene-acrylic emulsion or pure acrylic emulsion; and / or

[0023] The glass microbeads have a particle size of 0.05-10 μm; and / or

[0024] The plasticizer is at least one of starch ether, polyvinyl alcohol or polyethyleneimine; and / or

[0025] The penetrant is at least one of OP-10, Tween-20, fatty alcohol polyoxyethylene ether, and sodium dioctyl sulfosuccinate.

[0026] Preferably, the method for preparing the modified polymer emulsion comprises the following steps:

[0027] 1) Mix and stir aluminum dihydrogen phosphate, lithium magnesium silicate, glass microspheres and ionized water to obtain a gel suspension;

[0028] 2) adding the silane coupling agent solution to the gel suspension obtained in step 1) under stirring, heating and stirring, and then standing to obtain a mixed suspension;

[0029] 3) The penetrant, plasticizer and polymer emulsion are uniformly mixed to obtain a mixed emulsion, and the mixed suspension obtained in step 2) is mixed with the mixed emulsion to obtain a modified polymer emulsion.

[0030] Preferably, the weight ratio of the mixed suspension to the mixed emulsion is 2:1.

[0031] Preferably, in step 2), the heating temperature is 50-55° C., and the stirring time is 30-40 min.

[0032] In a second aspect, the present invention also provides a method for preparing any of the above-mentioned track plate anchor mortars, using the following scheme:

[0033] The preparation steps are as follows: mix cement, mineral admixture, fine aggregate, water reducing agent, retarder, expansion agent, water retaining agent, anti-cracking fiber, waterproofing agent, and steel bar preservative evenly, then add modified polymer emulsion and water and stir to obtain anchor mortar.

[0034] The method for preparing the track slab anchor sealing mortar provided by the present invention mixes the raw materials in a step-by-step manner to increase the compatibility between the components and make the components evenly dispersed in the coating raw materials, so as to give full play to the role of each component and maintain stability in the process of preparing the anchor sealing mortar.

[0035] The working principle and beneficial effects of the present invention are:

[0036] 1. In the present invention, the amount of water used for mixing the anchor mortar is changed by using a modified polymer emulsion, thereby adjusting the setting time of the anchor mortar. When used in areas with large temperature differences, the amount of the rheology-modified polymer emulsion can be appropriately increased when the temperature is high, and the amount of the rheology-modified polymer emulsion can be appropriately reduced when the temperature is low, so as to offset the effect of the temperature difference on the setting time of the anchor mortar and ensure the consistency of the operation time during construction.

[0037] 2. The modified polymer emulsion in the present invention includes glass microspheres, aluminum dihydrogen phosphate and lithium magnesium silicate. The glass microspheres are microsphere structures, the lithium magnesium silicate is a layered structure, and aluminum dihydrogen phosphate provides a certain viscosity-increasing effect, so that the modified polymer emulsion can enhance the lubrication effect and extrusion lubricity of the anchor mortar.

[0038] 3. Anti-cracking fibers and water-retaining agents are added to the anchor-sealing mortar of the present invention. The combined effect of the anti-cracking fibers and the water-retaining agent can ensure that the state of the anchor-sealing mortar before solidification will not be affected by temperature changes, thereby reducing the phenomenon of self-dehydration shrinkage and cracking. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0040] raw material:

[0041] Aluminum dihydrogen phosphate: The manufacturer is Shijiazhuang Xinsheng Chemical Co., Ltd.;

[0042] Lithium magnesium silicate: The manufacturer is BYK Additives (Shanghai) Co., Ltd.;

[0043] Glass beads: The manufacturer is Hebei Yilei Mining Co., Ltd.;

[0044] Tween-20: The manufacturer is Jiangsu Hai'an Petrochemical Plant;

[0045] Polyvinyl alcohol: The manufacturer is Changchun Chemical (Jiangsu) Co., Ltd.

[0046] Silicone acrylic emulsion: The manufacturer is Qingdao Dayang Haiderun Building Materials Co., Ltd.;

[0047] Sulphoaluminate cement: The manufacturer is Dengdian Group Cement Co., Ltd.;

[0048] Ordinary Portland cement: The manufacturer is Jinyu Cement;

[0049] S95 mineral powder: The manufacturer is Lingshou County Jieling Mineral Products Trading Co., Ltd.

[0050] Quartz sand: The manufacturer is Lingshou County Quanfeng Mineral Products Processing Plant;

[0051] Polycarboxylate water reducer: The manufacturer is BASF (China) Co., Ltd.

[0052] Boric acid: The manufacturer is Shandong Feihong New Materials Co., Ltd.

[0053] Calcium sulphoaluminate expansion agent: The manufacturer is Zhengzhou Jianwen Special Materials Technology Co., Ltd.;

[0054] Cellulose ether: The manufacturer is Shandong Heda Group Co., Ltd.

[0055] Polyacrylamide: The manufacturer is Jiangyin Lingrun Chemical Technology Co., Ltd.;

[0056] Glass fiber: The manufacturer is Renqiu Zhiyuan Chopped Fiber Factory;

[0057] Zinc stearate: The manufacturer is Tianjin Dingshengxin Chemical Co., Ltd.;

[0058] Benzotriazole: The manufacturer is Jinan Aoxing Chemical Co., Ltd.;

[0059] Silane coupling agent: Model is KH570, manufacturer is Shandong Huachen New Materials Co., Ltd.

[0060] Preparation Example

[0061] A modified polymer emulsion, the preparation steps of which are as follows:

[0062] 1) Mix 3.5 kg of aluminum dihydrogen phosphate, 4 kg of lithium magnesium silicate, 10 kg of glass beads and 45 kg of deionized water to obtain a gel suspension;

[0063] 2) Take 1.5 kg of 20% hydrolyzed silane coupling agent solution and add it to the gel suspension prepared in step 1) under stirring, heat to 40° C. and stir for 30 min, then let it stand for 3-4 h to obtain a mixed suspension;

[0064] 3) Take 0.5 kg of Tween-20, 2.5 kg of polyvinyl alcohol and 30 kg of silicone acrylic emulsion and mix them evenly to obtain a mixed emulsion. The mixed suspension prepared in step 2) is mixed with the mixed emulsion in a mass ratio of 2:1 to obtain a modified polymer emulsion.

[0065] Among them, the particle size of the microbeads is 5 microns.

[0066] Example

[0067] Example 1

[0068] A track plate anchor mortar and preparation method:

[0069] S1. 40kg sulphoaluminate cement, 10kg ordinary Portland cement, 10kg mineral powder, 50kg quartz sand, 2kg polycarboxylic acid water reducer, 3kg boric acid, 3kg calcium sulphoaluminate expansion agent, 1kg cellulose ether, 1.5kg polyacrylamide, 0.2kg glass fiber, 2kg zinc stearate, 1kg benzotriazole were mixed to obtain a mixture;

[0070] S2. Add 13 kg of the modified polymer emulsion to the mixture prepared in S1, mix well, and obtain anchor mortar.

[0071] Among them, the sulphoaluminate cement is type 52.5 sulphoaluminate cement; the ordinary Portland cement is type 52.5 ordinary Portland cement; the mineral powder is grade S95 mineral powder; and the quartz sand is 40-80 mesh quartz sand.

[0072] Embodiment 2-6

[0073] The sealing and anchoring mortars of Examples 2-6 include the raw materials in parts by weight as shown in Table 1.

[0074] Table 1 Raw materials and weight parts of the anchor mortar in Examples 2-6

[0075]

[0076]

[0077] Comparative Example

[0078] The anchor sealing mortars of Comparative Examples 1-5 include the raw materials in parts by weight as shown in Table 2. The difference from Example 1 is the parts by weight of each component, and the remaining steps are the same as those of Example 1.

[0079] Table 2 Raw materials and weight parts of anchor mortar in comparative examples 1-5

[0080]

[0081]

[0082] Performance testing

[0083] Test example

[0084] For Examples 1-6 and Comparative Examples 1-5, test specimens were prepared according to the molding method in 7.2 of GB / T 17671-1999 "Cement mortar strength test", and three groups of test specimens were prepared in each group. The test specimens were cured according to 8. The three groups of test specimens were cured for 1d, 7d, and 28d, respectively. After reaching the specified age, the compressive strength was tested according to the method in 9 test procedure.

[0085] According to the determination of initial setting time in 8.3 of GB / T 1346-2011 "Water consumption and setting time of cement standard consistency", the operation time (initial setting time) of Examples 1-6 and Comparative Examples 1-5 was measured.

[0086] The measurement results are shown in Table 3.

[0087] Table 3 Measurement results of Examples 1-6 and Comparative Examples 1-5

[0088]

[0089]

[0090] It can be seen from the results of Examples 1-3 in Table 3 that, at the same ambient temperature, the operation time of the anchor mortar can be adjusted by changing the amount of the rheology-modified polymer emulsion.

[0091] It can be seen from the results of Examples 4-6 that, under different ambient temperatures, the consistency of the operating time of the anchor mortar can be maintained by changing the amount of the rheology-modified polymer emulsion.

[0092] According to the results of Comparative Examples 1-3, it can be seen that simply changing the amount of polymer emulsion can adjust the setting time of the anchor mortar, but it has a greater impact on the extrusion lubricity and plasticity of the mortar. Combined with the results of Comparative Example 4, if only water-retaining components are added without adding anti-cracking fibers, slight cracking may occur. Combined with the results of Comparative Example 5, when neither water-retaining components nor anti-cracking fibers are added, the cracking is more serious.

[0093] In summary, the anchor mortar provided by the present invention uses a modified polymer emulsion to change the mixing water amount of the anchor mortar, thereby adjusting the setting time of the anchor mortar. When used in areas with large temperature differences, the amount of the rheology-modified polymer emulsion can be appropriately increased when the temperature is high, and the amount of the rheology-modified polymer emulsion can be appropriately reduced when the temperature is low, so as to offset the effect of the temperature difference on the setting time of the anchor mortar and ensure the consistency of the operation time during construction. The modified polymer emulsion can enhance the lubrication effect and extrusion lubricity of the anchor mortar. At the same time, anti-cracking fibers and water-retaining agents are added to the anchor mortar in the present invention. The composite effect of the anti-cracking fibers and water-retaining agents can ensure that the state of the anchor mortar before solidification will not be affected by temperature changes, thereby reducing the phenomenon of self-dehydration shrinkage and cracking.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A track plate anchor mortar, characterized in that: It is composed of the following raw material components in parts by weight: 40-60 parts of cement, 0-20 parts of mineral admixture, 40-50 parts of fine aggregate, 0.1-0.8 parts of water reducing agent, 0.2-1 parts of water retaining agent, 0.1-0.5 parts of anti-cracking fiber, 1-3 parts of expansion agent, 0.3-1 parts of waterproofing agent, 0.2-1 parts of steel bar rust inhibitor, 0-4 parts of retarder, 10-18 parts of modified polymer emulsion; The modified polymer emulsion includes a polymer emulsion and the following raw material components in parts by weight: 3-8 parts of aluminum dihydrogen phosphate, 5-10 parts of magnesium aluminum silicate, 10-20 parts of glass microspheres, 52-77 parts of deionized water, 5-10 parts of silane coupling agent solution, 1-3 parts of penetrant, and 10-20 parts of plasticizer; The preparation method of the modified polymer emulsion comprises the following steps: 1) Mix and stir aluminum dihydrogen phosphate, lithium magnesium silicate, glass microbeads and deionized water to obtain a gel suspension; 2) Add the silane coupling agent solution to the gel suspension prepared in step 1) under stirring, heat and stir, and then let stand for 3-4 hours to obtain a mixed suspension; 3) uniformly mixing the penetrant, plasticizer and polymer emulsion to obtain a mixed emulsion, and mixing the mixed suspension obtained in step 2) with the mixed emulsion to obtain a modified polymer emulsion; The weight ratio of the mixed suspension to the mixed emulsion is 2:1; The water retaining agent is at least one of cellulose ether and polyacrylamide; The anti-cracking fiber is at least one of polypropylene fiber, glass fiber and basalt fiber.

2. A track plate anchor sealing mortar according to claim 1, characterized in that: The water reducer is at least one of a melamine-based water reducer, an aminosulfonate-based water reducer or a polycarboxylic acid-based water reducer; and / or The expansion agent is at least one of a UEA expansion agent, a calcium sulfoaluminate expansion agent or a magnesium oxide expansion agent; and / or The waterproofing agent is at least one of modified sheet silicate, sodium methyl silicate, potassium methyl silicate or zinc stearate; and / or The steel bar rust inhibitor is at least one of benzotriazole, calcium nitrite or fatty alcohol amine; and / or the retarder is at least one of sucrose, gluconic acid, boric acid, tartaric acid or sodium pyrophosphate.

3. The track slab anchor sealing mortar according to claim 1, characterized in that: The cement is at least one of ordinary Portland cement, sulphoaluminate cement or aluminate cement; and / or The mineral admixture is at least one of mineral powder, tailings powder, fly ash or silicon powder; and / or the fine aggregate is at least one of river sand, quartz sand, mineral sand or calcium sand.

4. The track slab anchor sealing mortar according to claim 1, characterized in that: The polymer emulsion is at least one of epoxy emulsion, polyurethane emulsion, phenolic resin emulsion, silicone emulsion, vinyl resin emulsion, silicone-acrylic emulsion, styrene-acrylic emulsion or pure acrylic emulsion; and / or The glass microbeads have a particle size of 0.05-10 μm; and / or The plasticizer is at least one of starch ether, polyvinyl alcohol or polyethyleneimine; and / or The penetrant is at least one of OP-10, Tween-20, fatty alcohol polyoxyethylene ether, and sodium diisooctyl sulfosuccinate.

5. The track slab anchor sealing mortar according to claim 1, characterized in that: The silane coupling agent solution is obtained by dropping the silane coupling agent into deionized water at a concentration of 20% and stirring for hydrolysis.

6. The track slab anchor sealing mortar according to claim 1, characterized in that: In step 2), the heating temperature is 50-55° C. and the stirring time is 30-40 min.

7. A method for preparing a track plate anchor mortar according to any one of claims 1 to 6, characterized in that: The preparation steps are as follows: mix cement, mineral admixture, fine aggregate, water reducing agent, retarder, expansion agent, water retaining agent, anti-cracking fiber, waterproofing agent, and steel bar rust inhibitor evenly, then add modified polymer emulsion and stir and mix evenly to obtain track plate anchor mortar.

Citation Information

Patent Citations

  • Track board sealing anchor mortar and preparation method thereof

    CN104150836A

  • Recycled-aggregate ready-mixed mortar

    CN106348679A

  • Anti-seepage concrete material in plateau region and preparation method of concrete material

    CN110156405A